Policy Implementation of Business Capital Loan Program by Community Self-Reliance Agency in Community Economic Empowerment in Cirebon City - Giri Cahya Pangestu; Moch. Taufik Hidayat; Nursahidin Nursahidin (Syntax Corporation Indonesia, 2026)
This study examines the implementation of the business capital loan policy managed by the Community Self-Reliance Agency (Badan Keswadayaan Masyarakat/BKM) and its contribution to community economic empowerment in Cirebon City by analyzing the implementation process, supporting factors, obstacles, and improvement efforts. A qualitative approach with a case study design was employed, focusing on Karyamulya and Kecapi Urban Villages. Data were collected through in-depth interviews, field observations, and document analysis as the primary sources of empirical information. The data were analyzed using George C. Edwards III's policy implementation model. The findings indicate that the implementation of the program has not yet fully achieved its objective of promoting community economic empowerment due to various implementation constraints. The policy implementation remains suboptimal, particularly in terms of communication, resources, and bureaucratic structure. Inadequate communication has led to the perception that the revolving funds are grants rather than loans, resulting in a low repayment rate. Although the program has improved access to business capital for micro-entrepreneurs, its contribution to long-term economic self-reliance remains limited. The study concludes that the success of the program depends not only on the availability of financial resources but also on the quality of policy implementation, institutional capacity, and sustainable program management